Analysis of the Role of Bundo Kanduang in Women's Representation in 50 Kota Regency - Jalius, As'ad Albatroy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research provides an overview of a study that investigates the role of Bundo Kanduang in enhancing women's representation and empowerment in the 50' Kota Regency of West Sumatra, Indonesia. Bundo Kanduang is a traditional Minangkabau institution that plays a significant part in the social, cultural, and political life of the Minangkabau community. This research delves into how Bundo Kanduang's role has influenced the participation of women at that regency. The study employs qualitative research methods, including interviews, focus group discussions, and document analysis, to collect data on the experiences and perspectives of women in the 50' Kota Regency. The research explores the historical development of Bundo Kanduang, its organisational structure, and its contemporary role in women's lives. Preliminary findings suggest that Bundo Kanduang has evolved, adapting to changing cultural and political contexts. It has played a crucial role in preserving Minangkabau cultural traditions and promoting women's involvement in decision-making processes at the community level. However, it also faces challenges and criticisms, particularly related to its role in gender issues. The research project aims to provide a more comprehensive understanding of Bundo Kanduang's impact on women's lives and the potential for future improvements in women's representation and empowerment.Penelitian ini memberikan gambaran studi yang menyelidiki peran Bundo Kanduang dalam meningkatkan keterwakilan dan pemberdayaan perempuan di Kabupaten 50' Kota Sumatera Barat, Indonesia. Bundo Kanduang merupakan lembaga adat Minangkabau yang mempunyai peranan penting dalam kehidupan sosial, budaya, dan politik masyarakat Minangkabau. Penelitian ini menggali bagaimana peran Bundo Kanduang mempengaruhi partisipasi perempuan di kabupaten tersebut. Penelitian ini menggunakan metode penelitian kualitatif, meliputi wawancara, diskusi kelompok terfokus, dan analisis dokumen, untuk mengumpulkan data tentang pengalaman dan perspektif perempuan di Kabupaten 50' Kota. Penelitian ini mengeksplorasi sejarah perkembangan Bundo Kanduang, struktur organisasinya, dan peran kontemporernya dalam kehidupan perempuan. Temuan awal menunjukkan bahwa Bundo Kanduang telah berkembang seiring berjalannya waktu, beradaptasi dengan perubahan konteks budaya dan politik. Lembaga ini memainkan peran penting dalam melestarikan tradisi budaya Minangkabau dan mendorong keterlibatan perempuan dalam proses pengambilan keputusan di tingkat masyarakat. Namun, lembaga ini juga menghadapi tantangan dan kritik, khususnya terkait peran mereka dalam isu gender. proyek penelitian ini bertujuan untuk memberikan pemahaman yang lebih komprehensif tentang dampak Bundo Kanduang terhadap kehidupan perempuan dan potensi perbaikan keterwakilan dan pemberdayaan perempuan di masa depan.